Timor-Leste Government Policies Toward Government Land Used by Foreign Companies - Da Costa Fernandes Hornai, Honorio (Syntax Corporation, 2026)
This study examines government policies related to state land management, focusing on land use by foreign companies within the legal framework of Timor-Leste. State land is a critical issue tied to state sovereignty and the regulation of natural resource utilization. This study aims to explore the land asset regulation system under the Constitution of the Democratic Republic of Timor-Leste (RDTL), as well as the government's role in managing state land. It also aims to analyze the legal basis for the nationalization of state assets and the challenges in implementing this policy. Employing a normative legal research approach, this study examines laws and regulations governing land ownership and use in Timor-Leste, along with government policies on state land management. The findings reveal that the Timor-Leste government, through the National Directorate of Land and Property of the Ministry of Justice, has endeavored to regulate land ownership, including a policy of nationalizing state assets involving land owned by foreign companies. However, significant challenges persist in implementation, particularly suboptimal law enforcement. Effective land policy implementation in Timor-Leste requires a more systematic approach to managing and administering state assets. More intensive efforts are needed to enforce existing regulations, ensuring this policy can be implemented effectively—especially in land management involving foreign companies under the framework of state sovereignty.